Synthesis, antifungal and antibacterial activity of novel 1,2,4-triazole derivatives - Deepa Gupta; D K Jain (Wolters Kluwer Medknow Publications, 2015)
A large number of 1,2,4-triazole-containing ring system have been incorporated into a wide variety of therapeutically interesting drug candidates including anti-inflammatory, central nervous system stimulants, antianxiety, and antimicrobial agents. To overcome the rapid development of drug resistance, new agents should preferably have chemical characteristics that clearly differ from those of existing agents. Thus led to the design and synthesize the new antimicrobial agents. A novel series of Schiff bases based on of 4-(benzylideneamino)-5-phenyl-4H-1,2,4-triazole-3-thiol scaffold was prepared by heating thiocarbohydrazide and substituted benzoic acid and subsequently, treating with substituted benzaldehydes. Seventeen derivatives were synthesized and were biologically screened for antifungal and antibacterial activity. The newly synthesized derivatives of triazole showed antifungal activity against fungal species, Microsporum gypseum; and antibacterial activity against bacterial species, Staphylococcus aureus. It was observed that none of the compounds tested showed positive results for fungi Candida albicans fungi Aspergillus niger, nor against bacterial strain Escherichia coli. Strong antifungal effects were obtained for the synthesized compounds against M. gypseum and were superior or comparable to standard drug ketoconazole. Similarly, all of the synthesized compounds exhibit strong antibacterial activity against S. aureus and were superior or comparable to standard drug streptomycin. It was found that among the triazole derivatives so synthesized, six of them, showed antifungal activity superior to ketoconazole while one of them, showed antibacterial activity superior to streptomycin. Thus, these can be the potential new molecule as an antimicrobial agent.